2010
DOI: 10.1016/j.bjmsu.2009.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Successful Trial without Catheter in Acute Urinary Retention

Abstract: We aim to identify predictors of successful trial without catheter after an episode of acute urinary retention and to evaluate how serum prostate specific antigen (PSA) and C-reactive protein (CRP) levels behave during an acute urinary retention episode and also whether the PSA level is a useful indicator of undetected prostate cancer. Patients and methods: 335 patients presented to our institution in acute urinary retention from June 2006 to December 2007. After excluding females, patients with known prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
1
13
1
Order By: Relevance
“…Lim et al [18] reported on 79 men with first spontaneous AUR, for which RV >800 mL correlated with failure, but no statistical significance was reported. A similar finding without statistical significance was reported by Zeif et al [9] for about 100 cases with median RV of 750 mL. Higher volumes (mean, 916 mL) resulted in lower success rates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Lim et al [18] reported on 79 men with first spontaneous AUR, for which RV >800 mL correlated with failure, but no statistical significance was reported. A similar finding without statistical significance was reported by Zeif et al [9] for about 100 cases with median RV of 750 mL. Higher volumes (mean, 916 mL) resulted in lower success rates.…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate regression analysis confirmed this (odds ratio, 1.92; 95% CI, 1.52 to 2.42; P<0.001). In a prospective audit of 100 patients who underwent TWOC without α-blockers, volume on USG was not considered [9]. Success was more likely in patients with smaller glands (P=0.004).…”
Section: Discussionmentioning
confidence: 99%
“…A French cross sectional study of 2 618 patients showed that 72.8% of patients had TWOC after a median of 3 days catheterization and if first TWOC failed, 33.4% had second TWOC before considering surgical intervention . There are various studies in English literature identifying the parameters which predicts the successful TWOC for AUR . The present study further contributes to the current knowledge by exploring the cut‐off values of the parameters that predicts successful TWOC with their sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 77%
“…Hastie et al showed that patients less than 65 years had a more chances of positive outcome although it was not statistically significant. Mariappan et al found no association between TWOC outcome and age.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation